Peroral endoscopic myotomy for Jackhammer esophagus: to cut or not to cut the lower esophageal sphincter - Bechara, Robert; Ikeda, Haruo; Inoue, Haruhiro (Endoscopy International Open, 2016)
Background and study aims: With the success of peroral endoscopic myotomy (POEM) in treatment of achalasia, its successful application to other spastic esophageal motility disorders such as Jackhammer esophagus has been noted. The question of whether the lower esophageal sphincter (LES) should be included in the myotomy for Jackhammer esophagus is a topic of current debate. Here, we report our experience and results with four patients with Jackhammer esophagus treated with POEM. The clinical and manometric results are presented and their potential implications are discussed.Patients and methods: Between January 2014 and July 2015, four patients underwent POEM for treatment of Jackhammer esophagus at our center. Manometry was performed prior to and after POEM. All patients met the Chicago classification criteria for Jackhammer esophagus and received a barium esophagram and endoscopic examination before having POEM. Results: All patients had uneventful procedures without any intraoperative or post-procedure complications. Patients in which the LES was included during POEM had resolution or significant improvement in symptoms. One patient in whom the LES was preserved had resolution of chest pain but developed significant dysphagia and regurgitation. Subsequently this individual received a repeat POEM which included the LES, resulting in symptom resolution. Conclusions: POEM is a suitable treatment for patients with Jackhammer esophagus. Until there are larger-scale randomized studies, we speculate that based on our clinical experience and physiologic and manometric observations, obligatory inclusion of the LES is justified to reduce the risk of symptom development from iatrogenic ineffective esophageal motility or subsequent progression to achalasia.